New Opportunities for Determining the Terms of Carrying out the Control Coronarangiography after Percutaneous Coronary Intervention - D. A. Brusentsov; P. A. Shesternya (Acta Biomedica Scientifica, 2020)
Background. Coronary heart disease is the leading cause of death in the Russian Federation, causing social and economic damage to the state. Previously published studies showed the association of rs1800470 polymorphism of the gene of the transforming growth factor-β1 (TGF-β1) with the risk of developing coronary artery disease due to more severe atherosclerotic lesions of the coronary arteries. Aim of the research. To study the association of single-nucleotide polymorphism rs1800470 of the TGF-β1 gene with the rate of progression of atherosclerotic coronary artery lesion. Material and methods. The study included 89 men with myocardial infarction, a Caucasian race under the age of 65 years (51 ± 7.9). Genomic DNA was isolated from venous blood by the phenol-chloroform method. The rs1800470 polymorphism of the TGF-β1 gene was tested using real-time polymerase chain reaction (PCR) (TaqMan probes, AB 7900HT). Assessment of the severity of coronary lesion was carried out initially according to the standard polyprojection coronary angiography protocol with the Gensini score calculated, as well as in dynamics after 40.7 ± 29.7 months (from 5 to 103 months). Results. Carrier of the rs1800470 allele A of the TGF-β1 gene is an independent risk factor for coronary heart disease and is associated with a more aggressive course of coronary atherosclerosis in men: a 20 % worsening of the Gensini score was observed after 7 months (p = 0.013), and by 30 % after 5 months (p = 0.003) from the initial coronary angiography. In addition, the homozygous genotype AA rs1800470 of the TGF-β1 gene is associated with the development of late stent restenoses in this group of patients after 12 months of observation (p = 0.002). Conclusion. Identification of carriers of the rs1800470 allele A of the TGF-β1 gene can help identify patients at risk for more rapid progression of coronary artery atherosclerosis in order to conduct angiographic control in the early period – 6 months from the initial percutaneous coronary intervention.